A rare complication of knee hematoma after genicular nerve radiofrequency ablation. (May 2019) - Strand, Natalie; Jorge, Paolo; Freeman, John; D'Souza, Ryan S.
Abstract: Background: Genicular nerve radiofrequency ablation (RFA) is an intervention to treat patients with chronic knee pain who have failed previous conservative, pharmacologic, and surgical interventions. Vascular complications following interventional procedures of the knee are extremely rare. A delay in diagnosis may be detrimental for the viability of the affected limb and may ultimately require amputation. Case Presentation: A 76-year-old man with a history of severe bilateral knee osteoarthritis and grade 4 chondromalacia presented to our clinic with refractory, severe bilateral knee pain and received a bilateral genicular nerve RFA. He returned 4 days later with right medial thigh pain and a magnetic resonance imaging study revealing a hematoma along the anteromedial aspect of the right distal femoral diaphysis measuring 13.3 × 4.5 × 3.0 cm. After collaboration between pain medicine and orthopedic surgery services, decision was made to treat patient conservatively with rest, compression, elevation, ice application, tramadol, and gabapentin, but with close follow-up and a low threshold to intervene with diagnostic and therapeutic angiography with embolization if bleeding worsened; he reported resolution of his pain after a 4-day and 1-month follow-up. Conclusion: This is the first report describing iatrogenic vascular injury in the knee after a genicular RFA procedure. Pain medicine physicians should be aware of the vascular anatomy of the knee, particularly paying close attention to variations after previous surgeries. Future trials should investigate modalities that minimize vascular complications including concomitant use of ultrasonography with fluoroscopy and other forms of RFA including pulsed or cooled RFA.